Does consumer health-orientation affect the use of nutrition facts panel and claims? An empirical analysis in Italy. (December 2016) - Cavaliere, Alessia; De Marchi, Elisa; Banterle, Alessandro
Highlights: We explored the role of health-orientation on consumers' use of labelled information. Data were collected through face-to-face interviews and analyzed through OLS regressions. Highly health-oriented consumers are more likely to refer to nutrition facts panel. Low orientation to health is associated with high interest in claims. Abstract: Food labelling can play a key role in increasing consumers' food-related consciousness, and improving the healthiness of their food choices. However consumers' use of food labels is affected by a number of variables. The aim of this paper is to explore the role of health-orientation on consumers' use of different labelled information, making a distinction between mandatory and voluntary information (namely, nutrition facts panel vs nutrition and health claims). Data were collected in Italy through face-to-face interviews on a sample of 300 consumers in charge of their grocery shopping. To evaluate the relationship between health-orientation and label usage we developed an index strictly based on the definition of health-orientation itself and included such measure in our analysis, which is based on a set of OLS regressions. The main results overall stress the idea that different degrees of health-orientation are, indeed, reflected in a diverse use of labelled information. Highly health-oriented consumers are more likely to refer to the extensive information reported on nutrition facts panel, whereas claims are of main interest for consumers with low orientation to health. The results also strengthen the key role played by nutrition knowledge and education in favouring a frequent usage of the nutrition facts panel and confirm previous findings on the relationship between socio-economic status and consumers use of labelled information.